Supercapacitors: Stacked‐Layer Heterostructure Films of 2D Thiophene Nanosheets and Graphene for High‐Rate All‐Solid‐State Pseudocapacitors with Enhanced Volumetric Capacitance (Adv. Mater. 3/2017). Issue 3 (January 2017) - Wu, Zhong‐Shuai; Zheng, Yijun; Zheng, Shuanghao; Wang, Sen; Sun, Chenglin; Parvez, Khaled; Ikeda, Taichi; Bao, Xinhe; Müllen, Klaus; Feng, Xinliang
Abstract : Stacked‐layer heterostructure films of 2D thiophene nanosheets and graphene are constructed by Z.‐S. Wu, K. Müllen, X. L. Feng, and co‐workers, as described in article 1602960 for ultrahigh‐rate all‐solid‐state flexible planar micro‐supercapacitors with superior volumetric capacitance and ultrahigh scan rate due to the synergetic effect of the ultrathin pseudocapacitive thiophene nanosheets and the capacitive graphene.